Intentionalities and Resistances in English Language Learning: References to Design Effective Didactic Strategies - Jaime Romero, Berenice; Castillejos López, Willelmira; Reyes Toxqui, Alvaro (IE Revista de Investigación Educativa de la REDIECH, 2021)
The purpose of this article is to show the importance of the intentionalities and resistances that are built in the school environment as references to design effective English learning teaching strategies. The postulates are based on the integration of a theoretical model to understand the reality, which directed a descriptive-interpretative study of the teachers and students’ discourses, beliefs and meanings regarding to English teaching-learning in the Centro de Bachillerato Tecnológico Agropecuario No. 35 (CBTA No. 35) located in the municipality of Texcoco, State of Mexico. The findings –obtained through questionnaires, interviews, and a participatory workshop– allow us to conclude that, in the unconscious beliefs, discourses and meanings of the students, English is not significant and is reflected as an ideological element, which is far removed from their own worldview. Regarding the intentionalities and resistances of teachers and students, it was determined that they constitute areas of opportunity for educators to expand their fields of action and find new horizons oriented to allow students to give meaning to the English learning as a foreign language.